2021
DOI: 10.1001/jamanetworkopen.2021.18554
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Surveillance and Phylogenetic Analysis of SARS-CoV-2 Infection Among Hospital Health Care Workers

Abstract: IMPORTANCE It is unclear when, where, and by whom health care workers (HCWs) working in hospitals are infected with SARS-CoV-2. OBJECTIVE To determine how often and in what manner nosocomial SARS-CoV-2 infection occurs in HCW groups with varying exposure to patients with COVID-19. DESIGN, SETTING, AND PARTICIPANTS This cohort study comprised 4 weekly measurements of SARS-CoV-2-specific antibodies and collection of questionnaires from March 23 to June 25, 2020, combined with phylogenetic and epidemiologic trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 28 publications
2
35
0
1
Order By: Relevance
“… 17 The magnitude of regional differences in serostatus are also reflected by a serological study in HCW of the Amsterdam University Medical Centers between March and June, where the highest seroprevalence observed was 13.2% in HCW who were in direct contact with COVID-19 patients, vs 3.6% in HCW without direct patient contact, while the seroprevalence in our total study population was 21.1%. 18 At the beginning of the pandemic, the Southeast region of the Netherlands was considered a COVID-19 hotspot, while community transmission in Amsterdam was still low. Our data suggest most infections arise from the household, while Sikkens et al reported HCW working at COVID-19 wards to be at increased risk of infection, with transmission between HCW as a major contributor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 The magnitude of regional differences in serostatus are also reflected by a serological study in HCW of the Amsterdam University Medical Centers between March and June, where the highest seroprevalence observed was 13.2% in HCW who were in direct contact with COVID-19 patients, vs 3.6% in HCW without direct patient contact, while the seroprevalence in our total study population was 21.1%. 18 At the beginning of the pandemic, the Southeast region of the Netherlands was considered a COVID-19 hotspot, while community transmission in Amsterdam was still low. Our data suggest most infections arise from the household, while Sikkens et al reported HCW working at COVID-19 wards to be at increased risk of infection, with transmission between HCW as a major contributor.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest most infections arise from the household, while Sikkens et al reported HCW working at COVID-19 wards to be at increased risk of infection, with transmission between HCW as a major contributor. 18 Nevertheless, both studies indicate the potential impact of infection risks due to HCW-HCW interaction. Similar results were found by Steensels et al , 14 using the same study design, where most infections were most likely acquired in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Because of our relatively small number of IgG-positive subjects, we were unable to study specific risks for COVID-19 infections in our study group. A previous study of the acquisition of COVID-19 infection in healthcare workers showed that between March 2020 and June 2020, healthcare workers working in patient care areas were four times more likely to become infected with COVID-19 than those not working in patient care areas [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In short, follow-up visits were scheduled regularly (March, April, May, June, October 2020, January 2021) and included serological testing, surveys regarding results of nucleic acid amplification testing (NAAT), and presence of COVID-19 related symptoms since the previous visit. For comprehensive details about inclusion and follow-up of this cohort we refer to the original article of the S3 study [9].…”
Section: Methodsmentioning
confidence: 99%